2000
DOI: 10.1001/archpsyc.57.6.563
|View full text |Cite
|
Sign up to set email alerts
|

Children's Well-being 11 Years After the Chornobyl Catastrophe

Abstract: Given the multiple stressful experiences to which evacuee families were exposed, the small differences in the children's self-reports suggest that there are protective factors in the lives of these children. The trauma experienced by the mothers was reflected in their perceptions of their children's well-being, particularly somatic symptoms, but was not transmitted to the children themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(82 citation statements)
references
References 63 publications
3
75
0
2
Order By: Relevance
“…As expected they find a negative impact on happiness for individuals exposed to the catastrophe. Remennick (2002) analyzes the health of Chernobyl survivors that immigrated into Israel whereas Bromet et al (2000) focus on the happiness of local children that were infants or unborn at the time of the accident.…”
Section: Literaturementioning
confidence: 99%
“…As expected they find a negative impact on happiness for individuals exposed to the catastrophe. Remennick (2002) analyzes the health of Chernobyl survivors that immigrated into Israel whereas Bromet et al (2000) focus on the happiness of local children that were infants or unborn at the time of the accident.…”
Section: Literaturementioning
confidence: 99%
“…However, as of this writing, children also appear resilient in the aftermath of such accidents. Studies of the effects of the Three Mile Island near-meltdown in 1981, and of the Chernobyl disaster in 1986 (Cornely and Bromet, 1986;Bromet et al, 2000) have shown few long-term effects on indirectly exposed children so far. Bromet and colleagues also found that the main effects on the children were mediated by maternal anxiety or depression.…”
Section: Exposure To Distant Traumamentioning
confidence: 99%
“…Though less emphasized in the literature, it is important to consider the impact of threats to children on the level of stress experienced by parents. The impact of such stress may explain particularly the strong effects of major disasters on mothers of young children (Bromet et al, 2000;Laor et al, 2001). Efforts to prepare the general population for dealing with terrorism must consider the developmental range of responses, the possible differential sensitivity of mothers to dangers and threats to their children, and the salience of attachment figures for the psychological protection of children.…”
Section: Terrorism Risk and Interventions: A Developmental Resiliencementioning
confidence: 99%
“…[For more details, see Bromet et al (7).] Of 721 families with a child in the target age range, 693 resided in Kyiv in 1997 when the fieldwork took place.…”
Section: Subjects and Designmentioning
confidence: 99%